Analysis of Reading Difficulties of Muslim Student in Selangor, Malaysia - Hartanto, Edwin Dwi; Mahardani, Ardhana Januar; Cahyono, Hadi; Chaniago, Zamawi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The ability to read is one of the initial abilities that students from an early age must possess. This aims to improve students' ability to understand the information conveyed as well as knowledge in the learning process. However, there are still many problems with students' initial reading skills that limit students' ability to understand the information and knowledge provided, one of which is the problem of beginning reading skills faced by students in a guidance center in Hulu Langat, Selangor, Malaysia. This study aims to observe the problems of students' beginning reading skills in guidance workshops in Hulu Langat, Selangor, Malaysia. This study uses a type of qualitative research with a descriptive approach and data collection techniques through observation, interviews, questionnaires, and documentation studies. Data analysis was performed using data reduction techniques, data display, conclusions, and data confirmation. The results of the study showed that many students had difficulties in beginning reading. Some students cannot read the letters of the alphabet or spell words, while others do not know syllables, cannot read sentences, and cannot write letters of the alphabet A-Z. Internal and external factors that affect students' reading ability are also observed. Internal factors include students' ability to read and write, while external factors include the lack of parental attention and the lack of sufficient guidance. In conclusion, there needs to be more intensive efforts in helping students overcome initial reading difficulties.